Manajemen Kokurikuler dalam Projek Penguatan Profil Pelajar Pancasila di SMK Negeri 1 Klaten: Jurnal Artikel - Priyogo, Wulang (Media Manajemen Pendidikan, 2025)
The purpose of this research is to produce (1) an analysis of character education management in co-curricular programs in the Project for Strengthening Pancasila Student Profiles; (2) analysis of internal coordination in co-curricular programs in the Project for Strengthening Pancasila Student Profiles; (3) analysis of factors that support and hinder the management of co-curricular based character education and how to solve them; (4) analysis of the impact or changes in student character after participating in co-curricular programs in the Pancasila Student Profile Strengthening Project. This type of research is descriptive qualitative. Data collection techniques were obtained from interviews, observation and documentation. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, it can be concluded: (1) SMK Negeri 1 Klaten Regency through the P5 Team has implemented the four management functions (planning, organizing, implementing and supervising) very well in the co-curricular program in the Strengthening Pancasila Student Profile Project; (2) Internal coordination has been running regularly and well; (3) Supporting factors include school human resources, student guardians, and required funds. Inhibiting factors include schedule arrangements and student composition. This can be overcome with good communication and schedule arrangement by the class teacher; (4) The impact or change in character based on leadership values that have been prepared by the school can be felt by students and teachers. This positive impact has become an enthusiasm for implementing this school's superior program.